Ampacity and thermal equivalent modeling of subsea power cables for long distance power transmission and optimization - Duraisamy, Nishanthi (Nanyang Technological University, 2021)
One of the defining aspects of life in the modern world is the convenience of access to a dependable and plentiful supply of electricity. This essential utility is delivered to consumers from power generating stations via an extensive and intricate network of cables. Submarine power cables are becoming increasingly important to modern power transmission strategies. There has been a large amount of recent investment in projects such as offshore wind farms and international “megagrid" initiatives, of which submarine power cables are essential components. The installation and maintenance costs of such buried cables are far higher than the overhead lines due to the complexity involved. The cable construction and cooling system for the cables are not interchangeable with their overhead counterparts. The maximum allowable cable conductor temperature is limited to avoid cable failures. The maximum current carrying capacity (ampacity) of power cables depends on the heat transferability of its surrounding medium. Submarine power cable ampacity is calculated conventionally following the international standards defined for underground cables. This conservative approach results in the system over design and under-utilization of the cable capacity. In reality, the thermal behavior of submarine environments differs significantly from its underground counterpart as the porous sediments are constantly water-saturated. The research aims to model the electrical and thermal characteristics of such long distance cables for accurately determining the effect of the factors that influence the ampacity and optimize the power flow. The cable ampacity analyses were carried out using the standards defined in IEEE 835 and IEC 60287. Unrealistic simplifications used for calculating the heat dissipation from the cable limited the validity of the calculation to specific cable geometries. Consequently, the first challenge in this work was developing a general reliable numerical procedure for the analysis of thermal field characteristics of the subsea cable systems of any system geometry, backfill and submarine environment. The effect of the thermal circuit parameter variations was the main concern as it has a higher effect on the cable’s thermal behavior and it may result in a significant difference in the cable ampacity . In this regard, special attention was paid in developing a sensitivity methodology of thermal field with respect to the thermal parameter changes. The difficulties have arisen since the model developed here was based on the exact finite element implementation and did not involve any simplification for the thermal heat modeling. The finite element method (FEM) was used for determining the factors affecting ampacity of submarine power cables cable using the COMSOL Multiphysics software program. Complex multiple layered co-axial cables were analysed to determine the effect of sediment properties on the cables ampacity. Considerations of sediment properties to calculate external thermal resistance resulted in ampacity values significantly different from standard values. Lab-scale experimentation was conducted to validate the results. The inclusion of convective heat transfer obtained a more precise ampacity estimate compared to that of the standard methods. The findings are significant for submarine power cables where the occurrence of convective cooling is neglected in general.